Delineation of coaly source rock distribution and prediction of organic richness from integrated analysis of seismic and well data. (March 2021) - Sahoo, Tusar R.; Funnell, Robert H.; Brennan, Stephen W.; Sykes, Richard; Thrasher, Glenn P.; Adam, Ludmila; Lawrence, Mark J.F.; Kellett, Richard L.; Ma, Xiajing
Abstract: Coaly facies (coals, shaly coals and coaly mudstones) are the primary source rock in several important petroleum basins in SE Asia and Australasia. Delineating these facies and quantifying their organic richness within kitchen areas are some of the key risks for petroleum exploration. To improve their delineation and characterisation using seismic data, a case study was undertaken of the coal-bearing Paleocene and Eocene intervals within the Maari 3D seismic volume area, offshore southern Taranaki Basin, New Zealand. Supporting data were acquired from well logs (including borehole image logs), existing geochemical analyses of well cuttings, and new laboratory measurements of in-situ geophysical and geochemical properties of coal samples from onshore coal mines and other outcrops. In the Paleocene–Eocene interval in the Maari 3D, coaly facies display characteristic low density (<2.5 g/cc) and velocity (<4000 m/s) and appear as bright, resistive layers in image logs. To delineate these facies in the Maari 3D volume, a post-stack seismic inversion was carried out and a P-impedance (product of density and P-wave velocity) model was prepared. Coaly facies exhibit moderate–high amplitude and moderately continuous (up to ~5 km) seismic reflectors, with low P-impedance (<9000 m/s × g/cc) character. Interval P-impedance and amplitude maps reveal temporal variation in the distribution and abundance of coaly facies within the Paleocene–Eocene coastal plain depositional environment. A logarithmic relationship between P-impedance and TOC was used to convert average P-impedance maps to proxy TOC maps for five Paleocene–Eocene time intervals. Coaly facies are most abundant in the low P-impedance areas in the southwestern and central parts of the study area where average TOC is estimated up to 30 wt.%. P-impedance-derived estimates of TOC may be less reliable in structurally high areas hosting hydrocarbon-bearing sandstones and siltstones as some of these facies show similar P-impedance character to coaly facies. Highlights: A new method was developed to better delineate coaly facies from 3D seismic data. Relationships established between density, TOC and P-impedance of coaly rocks. Average P-impedance maps transformed to average TOC maps for seismic intervals. Improved quantification of coaly source rocks for petroleum systems modelling.